2020
DOI: 10.1088/1748-9326/ab7f64
|View full text |Cite
|
Sign up to set email alerts
|

Links between green space and public health: a bibliometric review of global research trends and future prospects from 1901 to 2019

Abstract: Considerable specific cross-sectional and review studies have linked exposure to green spaces to improving public health, but there is no bibliometric review attempting to systemically and retrospectively analyze these existing articles. Here we aim to uncover global research status, trends, and future prospects in green spaces and health (G-H) research then propose a framework for the underlying mechanisms and pathways that link green space to public health. We obtained 18 961 G-H research publications from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 129 publications
(96 citation statements)
references
References 96 publications
3
92
0
1
Order By: Relevance
“…For example, Eva Heinen et al pointed out that people prefer walking or cycling in paths with beautiful and greenerycovered scenes [40] . Studies also confirmed that physical activities in green spaces bring about more health benefits than activities 住地和公园绿地之间的欧氏距离或网络距离 [38] ,或通过网络地图的API 接口获取出行时间值。可视性指的是居民通勤出行时或者其住宅附近 绿地的可视情况,通常借助调研问卷的自我报告形式或Google地球街景 模式等方式获取 [36] 。 不同的"暴露"指标的选取,一定程度上依赖于城市绿地对人群 健康的作用途径 [7] happened in other (such as indoor) environments [1] . Moreover, along with physical activities, risks of chronic and metabolic diseases, e.g., cardiovascular diseases known as the "No.1 killer worldwide," could be decreased [11] .…”
Section: Physical Activity Encouragementmentioning
confidence: 73%
See 3 more Smart Citations
“…For example, Eva Heinen et al pointed out that people prefer walking or cycling in paths with beautiful and greenerycovered scenes [40] . Studies also confirmed that physical activities in green spaces bring about more health benefits than activities 住地和公园绿地之间的欧氏距离或网络距离 [38] ,或通过网络地图的API 接口获取出行时间值。可视性指的是居民通勤出行时或者其住宅附近 绿地的可视情况,通常借助调研问卷的自我报告形式或Google地球街景 模式等方式获取 [36] 。 不同的"暴露"指标的选取,一定程度上依赖于城市绿地对人群 健康的作用途径 [7] happened in other (such as indoor) environments [1] . Moreover, along with physical activities, risks of chronic and metabolic diseases, e.g., cardiovascular diseases known as the "No.1 killer worldwide," could be decreased [11] .…”
Section: Physical Activity Encouragementmentioning
confidence: 73%
“…The Constitution of the World Health Organization defines that health is a state of complete physical, mental, and social 1 引言 随着城市化的不断发展,人口从乡村流向城市,城市已成为人类 最主要的栖息地。然而,快速的城市化进程也带来了严峻的环境和人 群健康问题。快速的生活节奏、日益加大的社会竞争压力、多坐少动 等缺乏体力活动的生活方式,以及城市高密度发展所导致的绿色空间 的不断减少,成为引发各类精神疾病和慢性疾病的重要因素 [1]~ [3] 。"基 于自然的解决方案"(NBS)正是科学家为应对复杂的城市生态环境问 题和人群健康问题所提出的一项重要行动策略,旨在高效利用自然资 源,以有效且强适应的方式来应对一系列环境挑战,同时带来经济、 社会和环境效益 [4] 。作为一种创新的可持续设计理念,NBS强调从设计 实践层面实现理论价值,以达到城市韧性提升、人与自然和谐共处和 资源可持续利用的目的 [5] 。城市绿地作为城市中重要的自然资源,是 NBS的重要组成部分。城市绿地不仅为城市提供了广泛的生态系统服务 [6] , 也是居民亲近和感受自然的重要场所,能够缓解居民的生活和工作压 力、改善人群健康 [7]~ [9] 。玛娅•武伊契等人 [10] 通过跨学科方法研究了城 市自然环境与人群心理健康的关系,发现NBS能有效帮助改善实验参与 者的压力过大、抑郁和焦虑等状况;马蒂尔达•范•登•波什等人 [11] 则引入"NBS框架"综述了城市自然环境对人群健康的各类积极效益。 然而,当前的NBS研究多集中于探讨生态环境问题的缓解,仅有少量研 究将其与人类健康和福祉相互关联。因此,如何将城市绿地与人群健 康研究和NBS理论研究相结合仍有待深入探索。此外,现有研究虽然在 城市绿地与健康效益关系的探索上取得了诸多进展,但是,关于系统 构建城市绿地与人群健康之间复杂潜在作用途径的相关研究仍显欠 缺 [12]~ [14] ,这直接阻碍了城市绿地系统在规划设计层面的策略实施 [15] 。 鉴于此,本文通过论述城市绿地对人群健康的积极与消极影响, 构建了城市绿地促进人群健康的作用途径理论框架,最后从实践视角 提出了相应的城市绿地系统规划应对策略和启示,以期推动实现自然 解决方案的价值。 《世界卫生组织组织法》将"健康"定义为"不仅为疾病或羸弱 之消除,而系体格、精神与社会之完全健康状态" [16] 。据此可将"健 well-being and not merely the absence of disease or infirmity [16] , according to which it may cover physical health, mental health, and social health. A large collection of papers have studied the link between urban green spaces and public health via experimental research, case study, and longitudinal research.…”
Section: Impacts Of Urban Green Spaces On Public Healthunclassified
See 2 more Smart Citations
“…During the past few decades, rapid urbanization has significantly changed the way people live. The probability of urban inhabitants coming into touch with UGS has also been decreased (Zhang et al 2020). As a result, the detrimental effect of decreased interaction with UGS on public health and the health benefits of green space exposure have been discussed in several studies.…”
Section: Mental Health and Wellbeingmentioning
confidence: 99%